3*(2x-1)+7=5*(x-1)+7
3,1*(1-3t)+t=0,4*(t-14)
0,8*(0,5-2u)=2u+0,4
0,2*(x-3)-1=0,5*(x+3)-0,4
-5*(z-7)=30-(2z+1)
-2*(x+5)+3=2-3*(x+1)
3*(2x-1)+6x=10x-7
4n-2*(n+7)=2n-2*(n-1)

1

Ответы и объяснения

2014-04-01T15:14:35+04:00
1) 6x - 3 + 7 = 5x - 5 + 7 
   x = - 2 
2) 3,1 - 9,3t + t = 0,4t - 5,6
    8,7t = 8,7
     t = 1
3) 0,4 - 1,6u = 2u + 0,4 
    u = 0 
4) 0,2x - 0,6 - 1 = 0,5x + 1,5 - 0,4
   -0,3x = 2,7
    x = -9
5) -5z + 35 = 30 - 2z - 1 
    -3z = -6
     z = 2 
6) -2x - 10 + 3 = 2 - 3x - 3 
    x = 6 
7) 6x - 3 + 6x = 10x - 7 
   2x = - 4
   x = -2
8) 4n - 2n - 14 = 2n - 2n + 2 
   2x = 16
    x = 8